Advances in Drug Design: Techniques and Strategies - Bose, Preeta (AG Volumes, 2025)
Drug design is an ancient and intricate pharmaceutical discipline. Since Emil Fisher proposed at the end of the 19th century that the interaction between a medication and its receptor is similar to that between a key and a lock, many advancements have been achieved in the area of drug design. Drug design has steadily evolved into a logical, well-structured discipline with a strong theoretical foundation and real-world applications. Examine the many studies conducted by researchers on drug creation approaches and tactics in this page. According to the review, a number of methods, including metabolomics, genomics, and proteomics, complement other approaches well. Additionally, the most recent drug design techniques can be used to find drug molecules with higher target specificity, accuracy, and safety at a lower cost and in a shorter amount of time. Furthermore, recent drug development efforts across a variety of disorders heavily rely on "Computer-Aided Drug Design (CADD)" methodologies. Computer approaches have significantly accelerated the development and optimisation of potential therapeutic medications.